Deciphering regeneration through non-model animals: A century of experiments on cephalopod mollusks and an outlook at the future - De Sio, Fabio; Imperadore, Pamela (Frontiers in Cell and Developmental Biology, 2023)
The advent of marine stations in the last quarter of the 19th Century has given biologists the possibility of observing and experimenting upon myriad marine organisms. Among them, cephalopod mollusks have attracted great attention from the onset, thanks to their remarkable adaptability to captivity and a great number of biologically unique features including a sophisticate behavioral repertoire, remarkable body patterning capacities under direct neural control and the complexity of nervous system rivaling vertebrates. Surprisingly, the capacity to regenerate tissues and complex structures, such as appendages, albeit been known for centuries, has been understudied over the decades. Here, we will first review the limited in number, but fundamental studies on the subject published between 1920 and 1970 and discuss what they added to our knowledge of regeneration as a biological phenomenon. We will also speculate on how these relate to their epistemic and disciplinary context, setting the base for the study of regeneration in the taxon. We will then frame the peripherality of cephalopods in regeneration studies in relation with their experimental accessibility, and in comparison, with established models, either simpler (such as planarians), or more promising in terms of translation (urodeles). Last, we will explore the potential and growing relevance of cephalopods as prospective models of regeneration today, in the light of the novel opportunities provided by technological and methodological advances, to reconsider old problems and explore new ones. The recent development of cutting-edge technologies made available for cephalopods, like genome editing, is allowing for a number of important findings and opening the way toward new promising avenues. The contribution offered by cephalopods will increase our knowledge on regenerative mechanisms through cross-species comparison and will lead to a better understanding of the complex cellular and molecular machinery involved, shedding a light on the common pathways but also on the novel strategies different taxa evolved to promote regeneration of tissues and organs. Through the dialogue between biological/experimental and historical/contextual perspectives, this article will stimulate a discussion around the changing relations between availability of animal models and their specificity, technical and methodological developments and scientific trends in contemporary biology and medicine.